Pengembangan Aplikasi Pengenalan Tempat Wisata Kuliner Legendaris di Jakarta Menggunakan Teknologi Realitas Tertambah Berbasis Android - Alfin; Paramaresthi Windriyani (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this research is to develop an application for the introduction of legendary culinary attractions in Jakarta based on Android. In the application there is information about five legendary culinary attractions in Jakarta and 3D objects will be displayed building tourist attractions. This research uses MDLC (Multimedia Development Life Cycle) method which consists of concepts, design, material collecting, assembly, testing, and distribution. This application development using Unity Software. The result of this research is an application for the introduction of legendary culinary attractions in Jakarta based on Android with Augmented Reality technology. The application has been tested using Black Box with the results of the scene displayed and the button function can be used id accordance with the indicators of success.